DAMPAK KECERDASAN BUATAN DAN PEMBELAJARAN MESIN TERHADAP PENDIDIKAN: TINJAUAN BIBLIOMETRIK - Dewi Ratna Muchlisa Mandyara (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This study reviewed the artificial intelligence (AI) and machine learning (ML) literature in the educational field. Using a bibliometric approach, we collected 626 articles published in 2018–2022 from journals indexed in the Scopus database. VOSviewer software was employed to investigate the data and illustrate the most dynamic scientific researcher and published articles in terms countries, sources, documents, and authors. The research field is, therefore, intricate and scattered in every multiple fields. Conducting a bibliometric analysis, we aim at organizing the field quantitatively and somewhat abstractly. We employed citation analyses, co-occurrence analysis and co-authorization analyses to evaluate productivity and impact of extant research. Our results indicates that the top cited authors are Cukurova m.; Gresse von wangenheim c.; Rodriguez m.; Knox J. As for the top two countries contributing to the literature, they were the US and UK have started their research in an early stage and that’s followed by China and Spain. We recommend that future research ought to focus further on economics and management related topics.